2022
DOI: 10.1186/s13073-022-01055-5
|View full text |Cite
|
Sign up to set email alerts
|

Human liver single nucleus and single cell RNA sequencing identify a hepatocellular carcinoma-associated cell-type affecting survival

Abstract: Background Hepatocellular carcinoma (HCC) is a common primary liver cancer with poor overall survival. We hypothesized that there are HCC-associated cell-types that impact patient survival. Methods We combined liver single nucleus (snRNA-seq), single cell (scRNA-seq), and bulk RNA-sequencing (RNA-seq) data to search for cell-type differences in HCC. To first identify cell-types in HCC, adjacent non-tumor tissue, and normal liver, we integrated sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 76 publications
(154 reference statements)
0
25
0
Order By: Relevance
“…Several previous analyses have also indicated that some tumour prognostic models may predict HCC patient survival. However, the identification of tumour subtype needs whole‐transcriptome sequencing data, which may be challenging in real‐world practice 30,31 . We established a new CD8T‐RGPI from CD8 + T cell infiltration‐associated genes by calculating the risk score, which had same prediction abilities for prognostic outcomes of HCC patients compared with other prognostic models 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous analyses have also indicated that some tumour prognostic models may predict HCC patient survival. However, the identification of tumour subtype needs whole‐transcriptome sequencing data, which may be challenging in real‐world practice 30,31 . We established a new CD8T‐RGPI from CD8 + T cell infiltration‐associated genes by calculating the risk score, which had same prediction abilities for prognostic outcomes of HCC patients compared with other prognostic models 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of tumour subtype needs whole-transcriptome sequencing data, which may be challenging in real-world practice. 30,31 We established a new CD8T-RGPI from CD8 + T cell infiltration-associated genes by calculating the risk score, which had same prediction abilities for prognostic outcomes of HCC patients compared with other prognostic models. 32,33 Based on the characteristics of HCC patients, CD8T-RGPI exhibited a differential expression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The single-cell analysis demonstrated that an upregulation of the inhibitor of apoptosis MLX interacting protein-like (MLXIPL) was related to poor survival in HCC [148] . HCC survival was also deceased in association with a proliferating cell type identified in HCC tumors [149] .…”
Section: Heterogeneity Of Hccsmentioning
confidence: 99%
“…According to sc-RNAseq from human and mouse liver, these 12 receptors expressed different patterns in different cell types (Extended Data Fig. 5a-d) 35,36,37,38 . We then measured expression of these receptors in our models.…”
Section: Skeletal Muscle Irf4 Regulated Liver Metabolism Via Fstl1-di...mentioning
confidence: 99%